PENGARUH PERTUMBUHAN PERUSAHAAN, STRUKTUR MODAL, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Isabella Permata Dhani; A.A Gde Satia Utama (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2017)
The purpose of the research is to obtain empirical evidence about the impact of growth, capital structure and profitability to firm value. The sample in this research is manufacturing company which listed in Indonesia Stock Exchange during the period of 2013 –2015. The source of the data of this research was conducted from annual report and sustainability report. This research is using quantitative approach with multiple linear regression analysis method. The result in this research found that growth effect positively to firm value, capital structure effect negatively to firm value  and profitability effect positively to firm value.Keyword : Growth, Capital Structur, Profitability, firm value